Ligand-Enabled Meta-C–H Alkylation and Arylation Using a Modified Norbornene - Shen, Peng-Xiang; Wang, Xiao-Chen; Wang, Peng; Zhu, Ru-Yi; Yu, Jin-Quan (Journal of the American Chemical Society, 2015)
2-Carbomethoxynorbornene is identified as a more effective transient mediator to promote a Pd(II)-catalyzed meta-C(sp2)–H alkylation of amides with various alkyl iodides as well as arylation with previously incompatible aryl iodides. The use of a tailor-made quinoline ligand is also crucial for this reaction to proceed.